Pengembangan Sistem E-Commerce Berbasis OpenCart Sebagai Media Promosi Digital untuk Meningkatkan Daya Saing UMKM Makanan dan Kue Kering di Kec.Lubuk Basung - Salshavira, Najwabilla; Annas, Firdaus; Wati, Fatma (JOVISHE : Journal of Visionary Sharia Economy, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in the Indonesian economy, including in Lubuk Basung Subdistrict. One potential sector is the food and pastry business. Despite the huge opportunities, their marketing is often constrained by market access and means of promotion. Digital technology should be able to overcome these obstacles, but many MSME players still need assistance in digital marketing strategies, especially horeca marketing. The lack of access to online platforms makes it difficult for local products to compete. In fact, food and pastries from this region have uniqueness and high quality to be marketed more widely. This research aims to develop a website-based promotion system with e-commerce using OpenCart to increase MSME sales. The research method used is Research and Development (R&D) with the define-design-develop-disseminate model. This system has the main features of a product catalogue and web signaling, which facilitate promotion and marketing. The results showed that the implementation of OpenCart was able to improve the competitiveness of MSMEs by expanding market access and reducing marketing costs. With this system, MSMEs in Lubuk Basung can utilise digital technology more effectively. The implications of this study show that the use of OpenCart-based e-commerce not only increases sales, but also strengthens the position of MSMEs in digital competition. This system is expected to be a strategic solution for MSMEs in Lubuk Basung to face marketing challenges in the modern era